Gallbladder cancer spreading into the aberrant cystic duct: First literature report. (November 2021) - Iwasaki, Junji; Iida, Taku; Nagata, Keiji; Nakamura, Kojiro; Itami, Atsushi; Kyogoku, Takahisa
Abstract: Introduction and importance: Although variations from the standard anatomy of the extrahepatic bile ducts are common, duplication of the cystic duct draining a single gallbladder is an extremely rare variant. We herein describe the first report of gallbladder cancer spreading into the aberrant cystic duct. Case presentation: A 60-year-old female presented with upper abdominal pain, and she was diagnosed with gallbladder cancer. Intraoperatively, she was found to have a duplicated cystic duct draining a single gallbladder, and her cancer had spread into the aberrant cystic duct entering the anterior right hepatic duct. Right hepatectomy with extrahepatic bile duct resection was performed to achieve R0 resection. Clinical discussion: In the English literature, 28 cases of duplicated cystic duct draining a single gallbladder have been reported. However, no cases of gallbladder cancer have been described in these previous reports. Conclusion: We report the first case of gallbladder cancer spreading into the aberrant cystic duct. To perform an oncologically adequate operation, exact assessment of the biliary tree is essential not only preoperatively but also intraoperatively. Highlights: Duplication of the cystic duct draining a single gallbladder is rare in the anatomical variations of the biliary tract. A 60-year-old female with gallbladder cancer was found to have a duplicated cystic duct draining a single gallbladder. Her cancer had spread into the aberrant cystic duct entering the anterior right hepatic duct. We report the first case of gallbladder cancer spreading into the aberrant cystic duct.